Emerging Contaminants from Sewage Sludge Application in Agriculture: Bibliometric Analysis - Arriaga-Vázquez, Ana M.; Hidalgo-Moreno, Claudia I.; Martínez-Ríos, Osbaldo; Barrales-Brito, Edgar; Etchevers-Barra, Jorge D.; Bravo-Vinaja, Ángel (REVISTA TERRA LATINOAMERICANA, 2025)
The production of biosolids in wastewater treatment plants represents an environmental concern, as it increases in parallel with population growth. The literature reports research addressing the application of sludge in agriculture, raising concern about the ef fects of emerging contaminants (EC) that may be present in crops and soils. The aim of this study was to analyze, using bibliometric tools, trends in scientific production related to research on the application of sewage sludge in agriculture during the period from 1992 to 2024. An advanced search was conducted in Web of Science, specifically in the Science Citation Index Expanded and Social Science Citation Index databases, and an analysis of bibliometric indicators was performed in Excel and VOSviewer. A total of 277 registered papers published during the period under study (1992–2024) were obtained. Scientific production followed an exponential growth pattern (R² = 0.9124), indicating an increase in the number of articles published in these years of less than 2% from 1992 to 2011, followed by growth greater than 2%, in contrast to 2021, when the increase exceeded 10%. The author with the highest number of registered publications was Lapen D. R., while the most cited author was Huerta E. The journal with the most published articles was Science of the Total Environment, and the Chinese Academy of Sciences was the institution with the greatest number of registered publications and the highest level of collaboration with institutions in other countries. It is concluded that the growth of literature related to the application of sewage sludge to agricultural fields and its implications concerning EC has been exponential, and that numerous authors are actively publishing in this field of study.